STUDI TENTANG SUMBER BELAJAR PADA MATA PELAJARAN GEOGRAFI DI SMA N 2 KECAMATAN KOTO BARU KABUPATEN DHARMASRAYA - Wahyudi, Irwom - (Pendidikan Geografi, 2014)
The focus of this research problem is how learning resources on the subjects of geography in SMA 2 Koto Baru Dharmasraya Learning Year 2013/2014. The purpose of this study was to determine the presence of a study on the subject of geography SMA 2 Koto Baru Dharmasraya Learning Year 2013/2014. This study used a qualitative approach. This study was conducted in SMA 2 Koto Baru Dharmasraya When the study was planned in August-September 2014. The informants are principals, geography teachers, and students. Data collection techniques in this study was implemented using several techniques, namely, interview techniques, observation techniques, and technical documentation. Analysis using data reduction, data presentation, and conclusion. The existence of learning resources on the subjects of geography in SMA 2 Koto Baru Dharmasraya learning year 2013/2014 Learning from the aspects of the geography of learning supports, the principal manage learning resources well, teachers are entrusted to teachers who are competent in their field and have the experience and the students themselves have great enthusiastic in implementing the learning geography. Aspects of geography learning support materials, teaching materials supplied from the school that is at the library, instructional materials sought teachers from other places, as well as teaching materials from the teacher searched the internet, teachers integrate all existing instructional materials in accordance with the characteristics of the students. Aspects of the learning environment supporting geography, manicured environment, infrastructure is complete and intact, clean and comfortable environment, and the environment is far from the bustle of the vehicle. Aspects of geography learning tool to support learning, learning tools provided in the form 1 piece infocus, some fruit globe, and a few pieces of the map.